PERBEDAAN TINGKAT KESEHATAN BANK PEMERINTAH DENGAN BANK SWASTA NASIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Septiana, Dwi (Jurnal Ilmu Manajemen, 2016)
The purpose of this research was to determine the difference between the healtf of banks of the Bank with the Government of National Private Bank listed on the Indonesia Stock Exchange. The data used in this research is secondary data such as financial ratios derived from the financial statements of banks listed on the Indonesia Stock Exchange (BEI) in the period from 2005 to 2014. While the variables used are the performance financial measured by CAMEL consisting of the CAR, NPL, NIM, ROA, ROE, and LDR. The population in this research are all banking companies listed in Indonesia Stock Exchange with sample 3 government banks and 5 national private banks. The results of this research indicate that there is no difference in the health of banks of government banks and national private banks listed in the Indonesia Stock Exchange on indicators CAR, NPL, NIM. While indicators ROA, ROE, and LDR indicate there are differences in the health of banks of state banks and national private banks listed in the Indonesia Stock Exchange. The implications of this research are expected to be used as notes or corrections to maintain and improve the health of banks of both government banking and private banking